Experimentally determined distribution of fluorine and chlorine upon hydrous slab melting, and implications for F–Cl cycling through subduction zones. (15th December 2015) - Van den Bleeken, Greg; Koga, Kenneth T.
Abstract: Fluorine and chlorine are volatile elements known to be enriched in primitive arc magmas, and variations of F/Cl ratios can carry information about slab devolatilization processes. Recent experiments on the fractionations of these elements suggest that aqueous fluid has limited capacity to enrich the magma source region in F. Hence, it is difficult to explain observations of primitive arc magmas particularly rich in F. To complement previous experimental studies, we examined the fractionation of fluorine and chlorine during hydrous partial melting of subducting slab. Element-doped phase equilibria experiments were carried out in a complex chemical system at conditions equivalent to potential slab melting temperatures (750–1000 °C) across the amphibolite to eclogite facies transition (1.3–3 GPa). Partition coefficients of F and Cl between hydrous silicic melts and minerals were determined by electron microprobe and/or ion probe. Fluorine is compatible in amphibole ( D F amp/glass  = 1.18–1.85), and incompatible in garnet (0.034–0.140), clinopyroxene (0.059–0.505), and allanite (0.205–0.504). Hence, amphibole is an important F host, and can retain significant quantities of F in the solid residue of partial melting. On the contrary, Cl is incompatible, with D Cl mineral/glass generally decreasing from amphibole (0.079–0.625; one outlier at 1.87) to allanite (0.163), clinopyroxene (0.066–0.158), and garnet (0.031–0.153; outlier at 0.492). As a result, Cl is easily mobilized during partial melting. Fluorine and chlorine release during slab melting have been quantified by applying our partition coefficients to a non-modal batch melting model. The model shows that amphibole plays a key role in F/Cl fractionation during partial melting, while F/Cl is close to that of source for the melting of amphibole free eclogite. Moreover, the results from a flux-melting model employing several source compositions are compared to F and Cl abundances in primitive arc magmas. The observed variations are best described by variable additions of slab-derived aqueous fluids and hydrous melts to the mantle wedge melting region.